The Relationship between Weight Gain and The Anemia in The Third Trimester Pregnant Women in Sangkrah Surakarta Health Center Area - Bella Nadhifa; Rufidah Maulina; Amelya Augusthina Ayu Sari; Noviyati Rahardjo Putri; Siti Nurhidayati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Anemia during pregnancy is a blood disorder that occurs in pregnant women when hemoglobin (Hb) in the body is less than 11 gr / dl in the 1st and 3rd trimesters, and less than 10.5 gr / dl in the 2nd trimester. In Surakarta, there are 1,077 pregnant women with anemia (10.15%) in 2020, while in 2019 the number of pregnant women with anemia reached 10.51%. One of the factors causing anemia in pregnant women is nutritional status. The nutritional status of pregnant women can be measured by the mother's weight gain before pregnancy and during pregnancy. The purpose of this study was to determine the relationship between weight gain and the incidence of anemia in pregnant women in the III trimester in Sangkrah Surakarta Health Center area in 2022. This study used the cross sectional method. The population in this study was pregnant women in the third trimester which were 88 people in Sangkrah Health Center area. The sampling technique in this study was total sampling. Data analysis using Chi-square statistical tests. The results showed that most respondents with abnormal weight gain experienced anemia as many as 33 pregnant women (37.5%). The results of the Chi-square test analysis ρ-value of 0.025 α (0.05) which means that there is a relationship between weight gain and the incidence of anemia in pregnant women in the third trimester in Sangkrah Surakarta Health Center area. It is recommended that the community can play an active role in preventing anemia for pregnant women by paying attention to the nutritional needs of pregnant women based on the ideal weight gain to achieve a good nutritional status of pregnant women.